2017
DOI: 10.1016/j.biopsych.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Neurite Density Underlie White Matter Structure Abnormalities in First-Episode Psychosis

Abstract: Deficits in neurite density appear fundamental to abnormalities in white matter integrity in early psychosis. In the first application of neurite orientation dispersion and density imaging in psychosis, we found that processes compromising axonal fiber number, density, and myelination, rather than processes leading to spatial disruption of fiber organization, are implicated in the etiology of psychosis. This accords with a neurodevelopmental origin of aberrant brain-wide structural connectivity predisposing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 50 publications
4
58
0
Order By: Relevance
“…A further "executive" dimension on this interoceptive dimensional framework attempts to capture the degree to which an individual is able to flexibly attend to, and utilize, interoceptive information or can adaptively switch between interoceptive and exteroceptive representations. 11 The conscious perception of bodily sensations is an important yet broad topic. Most theoretical approaches to interoception and consciousness focus on the role of bodily processes for phenomenal selfhood, 8,[35][36][37] where interoceptive events provide a bodily anchor for experiences of selfhood.…”
Section: Dimensions Of Interoceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further "executive" dimension on this interoceptive dimensional framework attempts to capture the degree to which an individual is able to flexibly attend to, and utilize, interoceptive information or can adaptively switch between interoceptive and exteroceptive representations. 11 The conscious perception of bodily sensations is an important yet broad topic. Most theoretical approaches to interoception and consciousness focus on the role of bodily processes for phenomenal selfhood, 8,[35][36][37] where interoceptive events provide a bodily anchor for experiences of selfhood.…”
Section: Dimensions Of Interoceptionmentioning
confidence: 99%
“…122 Research is currently investigating the nature of interoceptive deficits associated with ASCs. Work in children is divergent, with one study suggesting that interoceptive accuracy is intact in autis-tic children and adolescents (aged [8][9][10][11][12][13][14][15][16][17], 123 while a subsequent study found that interoceptive accuracy, ascertained using heartbeat tracking, was markedly impaired in a comparable child and adolescent autistic sample. 52 Impaired interoceptive accuracy has also been shown in autistic adults, demonstrated using the heart beat tracking task, where significantly lower interoceptive accuracy scores were observed relative to a matched control group.…”
Section: Autism Spectrum Conditionsmentioning
confidence: 99%
“…The compartmental model of NODDI quantifies intracellular neurite density separately from orientation dispersion (Zhang et al, 2012a), which are otherwise indistinguishable in standard DTI measures (e.g., FA). The specific tissue property measures offered by NODDI are sensitive to microstructural changes in previous studies of brain development (Kunz et al, 2014;Chang et al, 2015;Kodiweera et al, 2016;Genc et al, 2018), psychosis (Rae et al, 2017) and neurodegeneration (Colgan et al, 2016;Slattery et al, 2017). We demonstrated that faster nondecision time was associated with higher NODDI-derived neurite density index in the superior segments of bilateral CST, including a part of the superior corona radiata and its connections to the precentral gyrus.…”
Section: Discussionmentioning
confidence: 64%
“…Neurons and dendrites play a central role in learning, memory, and diseases, particularly in neurodevelopmental disorders and neurodegenerative diseases; therefore, a parameter derived from axons and dendrites is of great importance in the assessment of disease diagnosis and treatment outcome. 11,21 Recently, biophysical modeling of diffusion MRI (dMRI) data provided sensitive parameters, such as neurite density. Neurite density is an estimate of the combined volume fraction of axons and dendrites, which shows a highly significant correlation with neurite density estimate based on quantitative stereology.…”
Section: Introductionmentioning
confidence: 99%